2015
DOI: 10.1590/s0102-053620150000200012
|View full text |Cite
|
Sign up to set email alerts
|

Aclimatização de Brassavola tuberculata com a utilização de ANA em diferentes substratos

Abstract: Um dos fatores limitantes da produção de mudas in vitro de orquídeas é a fase de aclimatização. Foi objetivo desse trabalho avaliar a sobrevivência e o crescimento inicial de Brassavola tuberculata (Orchidaceae) utilizando ácido naftaleno acético (ANA) e diferentes substratos durante a fase de aclimatização. Para tanto, foram utilizadas plantas provenientes de cultivo in vitro, cujo sistema radicular foi previamente imerso por 10 segundos nas soluções de 0,0; 0,5; 1,0; 1,5; 2,0; 2,5; 3,0; 3,5; 4,0 e 4,5 mg/L d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Ouro Negro is also commonly used by commercial orchid growers in Tocantins. Sousa et al (2015) reported that the greatest survival percentage (74%) of Brassavola tuberculata plants during acclimatization was achieved when using sphagnum as a substrate when compared to coconut fiber and a mix of sphagnum and coconut fiber (1:1 v/v). They argued that due to its physical properties, sphagnum provided better water retention as well as adequate porosity.…”
Section: Acclimatizationmentioning
confidence: 99%
“…Ouro Negro is also commonly used by commercial orchid growers in Tocantins. Sousa et al (2015) reported that the greatest survival percentage (74%) of Brassavola tuberculata plants during acclimatization was achieved when using sphagnum as a substrate when compared to coconut fiber and a mix of sphagnum and coconut fiber (1:1 v/v). They argued that due to its physical properties, sphagnum provided better water retention as well as adequate porosity.…”
Section: Acclimatizationmentioning
confidence: 99%
“…According to Miyata et al (2014), an efficient root growth process is related to high nitrogen, manganese and zinc concentrations in the composition of medium MS. The greater root formation presented by heterotrophic plants grown in vitro consisted in a desirable characteristic to improve acclimatization process efficacy, despite the low efficiency of the root system (Sousa et al, 2015).…”
Section: Values Depicted Inmentioning
confidence: 99%
“…Significant differences were observed between acclimatization media, the SPAD values were higher using coir (24.81) compared with sphagnum (20.35) at 150 DAT, the LL was greater in sphagnum (6.63 cm) media comparing LL with coir (5.22 cm) at 30 DAT, and the EC was greater in coir (469.67 ms) compared with sphagnum (375.00 ms) at 150 DAT (Table 2). Sousa et al (2015) found no significant differences in the number of leaves and roots of Brassavola tuberculata for the substrates sphagnum and coconut fiber. The same was observed in this experiment, in which there was no significant difference between treatments for the number of leaves in T. undulatum.…”
Section: Resultsmentioning
confidence: 64%